The Night Sky Brightness Measurement using OZT-ALTS Telescope based on Sky Quality Meter - Maharani, Gabriella; Malasan, Hakim L.; Prastyo, Hendra Agus; Yusuf, Aditya Abdilah; Oktaviandra, Adhitya (Current STEAM and Education Research, 2024)
Sky brightness is an important parameter in astronomical observations. The brightness of the sky is affected by the level of light pollution. The problem of light pollution is faced by observatories around the world, including the ITERA Lampung Astronomical Observatory (OAIL) which has an OZT-ALTS telescope (robotic telescope) that routinely makes observations of celestial objects and is not immune from light pollution, so it is necessary to observe the brightness of the sky to know the source of light pollution, the value and contour pattern of sky brightness. Measurements were carried out on April 9 2022 using Sky Quality Meter (SQM). SQM is directed to each coordinate point with an azimuth interval of 22.5° and altitude of 15°. The measurement data is used to create a contour map of the brightness of the night sky. The contour mapping results are compared with the All Sky Camera image. Based on the sky brightness contour map, at an azimuth of 90° – 360° and an altitude of 20° there are a number of sources of light pollution from street lights and buildings with a sky brightness value of 12,626 mag/arcsec2. The darkest sky area is from azimuth 22.5° – 90° and altitude 0° - 90°, the sky brightness value is 19.31 mag/arcsec2. Based on observations, the night sky at the OZT-ALTS Telescope is of the City Sky - Bright Suburban type (Bortle Scale), and the visual magnitude limit is less than 5 magnitudes. The All Sky Camera shows the source of light pollution visually and its contour pattern matches the contour pattern from measurements using SQM.